GOIÂNIA: O MITO DA CIDADE PLANEJADA - PELÁ, Márcia Cristina Hizim (2009)
Goiânia was the first planned city of Brazil in the twentieth century. Its building was a strategy of power that sought, in a regional context, to link the productive regions of the State of Goiás, mainly to the south and southwest regions, and to end the old family oligarchies and, in a national level, to bring the country to a new pattern of capitalist production; that means, it was the investment in the process of expansion of the capitalist system of production through the territory modernization. Thus, the city appears with well defined interests and political/economic functions. To make this project feasible, many resources were used, since political and economics agreements till marketing campaigns with the aim to promote the need for modernization. The new was the way. To reach this, nothing better than a new urban plan to retract, through the curves and lines, the progress, the growth and the integration of the hinterland in modern times. The Goiás of "Tropas and Boiadas" (Troop and Drove) by Hugo de Carvalho Ramos, should subjugate to the Treaty of Versailles of Atílio Correia de Lima. This attempt to overlay a culture on the other produced contradictions, considering that it wasn t take into account - or at least the importance was not understood - the fact that who composes a city are the social costumers. Even if a city plan is carefully prepared and agreed politically and economically, its deployment will carry the influence of several social groups that will compose it, fact that will cause the change of the meanings. Thus, it can be observed the creation of a myth and/or urban phenomenon on the modern and planned city in countries land which is based on an ideology of the subjetc city . To understand these assertions is necessary to break with the fragmented way of thinking the city, which conduces to the construction of a critical sight of the space that allows to come across the local and the global, the contradictions between rule and life, the interference of the cultural practices in an urban planning; anyway, that allows an integrated analysis in which theory and practice, perception and reason are complementary in order to understand through the landscape and through the social representation and daily life how the social and cultural practices, material and immaterial, incured directly on the appearance and on the content of Goiânia s territory in the period of 1930 to 1950, observing the changes or even the disfigurement of the original plan, which involves the conflict between rule and life